Applying Media Literacy in Literary Learning: Understanding Literature Through a 21st Century Lens: Pembelajaran sastra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to examine the application of media literacy in 21st century literary learning, considering the influence of technology and digital media on learning methods. Media literacy is important to help students understand literary works and enrich their learning experiences. The use of digital media such as films, social media, and web-based learning platforms can connect literary texts to broader social and cultural contexts, as well as develop critical thinking skills. This study uses a qualitative approach with literature studies and observations on the application of media literacy in literary learning. The results of the study show that media literacy can improve students' understanding of literary works, offer new ways of interpreting texts, and encourage critical engagement with media content. Digital technology also makes it easier to access interesting and relevant learning resources. Therefore, it is important to develop literary learning methods that are in accordance with technological developments so that students can understand literature in a more in-depth and contextual way.